Surface settlement prediction of short-distance double-hole tunnel based on stochastic medium theory optimization algorithm - Xu, Jianhang; Zhang, Xianmeng; Li, Xiaofeng; Wang, Binghua (Archives of Civil Engineering, 2026)
It is of great significance to predict the displacement and deformation of surface settlement during the construction of short-distance double-hole metro tunnels to prevent dynamic disasters caused by surface settlement during construction. The stochastic medium theory is studied in this paper, the optimal algorithm of stochastic medium theory is proposed, which is considered the tunnel section convergence mode, the tunnel space position and the different sections of the tunnel. The accuracy of settlement monitoring data and theoretical prediction values in tunnel construction is analyzed in combination with three engineering cases. The research shows that the applicable condition of the formula is space span ratio (L/B) less than 7; the stochastic medium simplified theoretical prediction curve and the settlement monitoring curve are better fitted, the maximum settlement position and the trend It is basically consistent with the settlement monitoring curve. The theoretical prediction curve settlement groove width is basically consistent with the settlement monitoring curve settlement groove width. The optimal algorithm and the settlement monitoring data have good consistency, which can provide some reference for the project.